Arterial supply to the cloacal bursa of the Lhoman White LSL lineage fowl (Gallus gallus Linnaeus, 1758) - Pedro Primo Bombonato (Biotemas, 2008)
A study has been carried out on the origin, number and disposition of the arterial branches supplying the cloacal bursas of 30 female fowl (Gallus gallus) of the Lhoman White LSL lineage, aged between eight and ten weeks. The right isquiadic artery was cannulated and injected with a 50% colored solution of Neoprene latex “450”. Next, the samples were fixed with a 10% formalin solution through deep intramuscular, subcutaneous and intracavitary injections for a period of at least 48 hours. Dissections confirmed that the cloacal bursa was supplied by direct branches from the right bursocloacal arteries in 29 cases (96.67%), the left bursocloacal arteries in 28 cases (93.33%), the right cloacal arteries in 13 cases (43.33%), and the left cloacal arteries in 15 cases (50%). The number of branches from the arteries, independent of their origin, varied from two to six. There were two branches in 5 cases (16.67%), three branches in 14 cases (46.67%), four branches in 3 cases (10%), five branches in 6 cases (20%), and six branches in 1 case (3.33%). The distribution of the vessels was unique in each sample.